Analysis of Murābaḥah Contract Implementation and Its Impact on Community Economic Empowerment: A Case Study of PT PNM Mekaar Syariah in Dawe, Kudus - Athika Nuuriya Janna; Nurani Puspa Ningrum; Muhammad Nur Salim (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
This study explores the implementation and impact of the murābahah bil wakālah financing scheme at PT PNM Mekaar Syariah Dawe Kudus on community economic empowerment, particularly among underprivileged women. The objective was to assess the effectiveness of this non-collateral financing model, its impact on business growth, and its alignment with sharīʿah principles. A qualitative case study methodology was used, combining interviews, field observations, and surveys. Findings indicate that the murābahah bil wakālah model expanded access to capital and fostered business growth, especially among women in rural communities. However, challenges related to sharīʿah compliance, particularly with the milkiyah (ownership) principle, were identified. Moreover, the program's success was closely tied to consistent mentoring, which declined after 2023, leading to weaker repayment discipline, lower sharīʿah literacy, and stagnation in some businesses. This study highlights that while murābahah financing can empower communities economically, its sustainability requires improved mentoring and enhanced understanding of sharīʿah principles among participants. The research suggests that the effectiveness of microfinance programs can be maximized through ongoing education and institutional support.